Age at maturity of Mediterranean marine fishes - TSIKLIRAS, A. C.; STERGIOU, K. I. (Mediterranean Marine Science, 2014)
In this review we collected data on the age at maturity (tm) and maximum reported age (tmax) for 235 stocks of Mediterranean marine fishes, belonging to 82 species, 37 families, 12 orders and 2 classes (Actinopterygii and Elasmobranchii). Among Actinopterygii (mean tm ± SD = 2.20 ± 1.43 y, n = 215), tm ranged from 0.3 y, for the common goby Pomatoschistus microps, to 12 y, for dusky grouper Epinephelus marginatus, while among Elasmobranchii (mean tm ± SD = 5.94 ± 2.47 y, n = 20), tm ranged between 2.7 y, for brown ray Raja miraletus, and 12 y for picked dogfish Squalus acanthias. Overall, the tmax ranged between 1 y, for transparent goby Aphia minuta, and 70 y, for wreckfish Polyprion americanus. The mean tmax of Actinopterygii (tmax ± SD = 10.14 ± 9.42 y) was lower than that of Elasmobranchii (tmax ± SD = 14.05 ± 8.47 y). The tm exhibited a strong positive linear relation with tmax for both Actinopterygii (logtm = 0.58 ´ logtmax – 0.25, r2 = 0.51, P < 0.001) and Elasmobranchii (logtm = 0.67 ´ logtmax – 0.006, r2 = 0.51, P = 0.007). The mean tm/tmax did not differ significantly with sex within Actinopterygii (ANOVA: F = 0.27, P = 0.60, n = 90; females: mean ± SD = 0.276 ± 0.143; males: mean ± SD = 0.265 ± 0.138) and Elasmobranchii (ANOVA: F = 1.44, P = 0.25, n = 10; females: mean ± SD = 0.499 ± 0.166; males: mean ± SD = 0.418 ± 0.133). Finally, the dimensionless ratio tm/tmax was significantly lower (ANOVA: F = 31.04, P < 0.001) for Actinopterygii (mean ± SD = 0.270 ± 0.135, n = 180) than for Elasmobranchii, (mean ± SD = 0.458 ± 0.152, n = 20), when stocks with combined sexes were excluded from the analysis.